Proteomic response of the rat liver in differential swimming modes. (30th January 2018) - Chen, Liang; Yang, Yanhua; Wang, Yiting; Qiu, Lipeng; Xia, Hengchuan; Wang, Aiai; Liu, Hailong; Shi, Hongfei; Chen, Keping
Summary: Moderate exercise helps improve competition results, providing a balanced muscle tone and biochemical activity, whereas excessive training disrupts the balance between training and recovery, causes harm to the organism, and leads to overtraining syndrome (OTS). To explore the mechanisms of different protein expressions during training and acquisition of immunity, we used proteomic analyses to investigate the differences of liver‐protein expressions between 2 swimming modes. Sprague‐Dawley rats were randomly divided into control (CT), fatigue training (FT), and exhaustive training (ET) groups, and liver tissues from each group were subjected to 2‐dimensional electrophoresis (2DE). A total of 4518 protein spots were detected in 9 replicates, and 45 protein spots exhibited a >2‐fold difference in expression ( P < .05), 31 of which was successfully identified by mass spectrometry. SERPINA3K expression decreased markedly during 2 stages from CT → FT and FT → ET, while DDT, RHOT1, and RBP4 decreased significantly only from CT → ET but not from the former 2 stages. By contrast, KRT8, PCBD1, KRT18, PRDX1, and ACY1A showed significant >2‐fold increase in expression in either the CT → FT or FT → ET stages. Bioinformatic analyses showed that among the identified proteins, 30.2%, 54.18%, and 15.62% were involved in biological processes, molecular functions, and cell composition, respectively. Notably, PCBD1, PRDX1, and PPP1CB were involved in redox processes, while PPP1CB was only expressed in the FT group. RGN, PSMB9, and AGT, commonly recognized as oxidative stress biomarkers, may involve in regulating homeostasis in the locomotor mode and may provide diagnostic criteria for the occurrence and prevention of exercise‐induced fatigue and OTS.